The relationship between self-regulated learning and student learning outcomes in applied mathematics courses - Ega Edistria; Darul Nurjanah; Abdul Azis Abdillah; Rimalia Anggraini (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to ascertain whether there is an interaction between self-regulating rules and student learning outcomes in applied mathematics courses. This study uses the product-moment correlation method from Karl Pearson. The research sample of 57 students was determined by convenience sampling. The data were obtained from questionnaires and midterm math scores. Data analysis methods use descriptive percentages, basic tests for linear regression, and SPSS version 16.0 for hypothesis testing. The findings of this research indicate that self-regulation has a solid and beneficial impact, correlated with the results of student learning in applied mathematics courses. The result of the calculation is the coefficient r xy = 0.721 > 0.005, with a determinant of 51.98%. The greater the degree of self-regulation, the more significant the learning outcomes obtained by students in applied mathematics courses.